The Impact of Government Interference to Religion on Religious Giving: Evidence from European Countries - ÇOKGEZEN, MURAT (SPRINGER, 2021)
While the impact of government interference to the religious domain has long been discussed in previous literature, empirical evidence on the nexus between government intervention to religion and individuals' giving to religious organizations remains limited. In this study, we aim to fill this gap and examine whether government intervention affects individuals' giving to faith-based charities. To this end, a survey data conducted in 20 European countries and two measures of government intervention to religion were used. Our empirical investigation based on multilevel logistic regression, after controlling for possible confounding factors at individual and country levels, indicates that government regulation of religion has a significant negative impact both on religious donation and volunteering. The findings of the present study add substantially to our understanding of nexus between government and religion and will serve as a base for future studies.
Keywords: Government regulation; Religious giving; Multilevel logit regression; Europe; STATE-REGULATION; DETERMINANTS; CHURCH; PARTICIPATION; CONTEXT; PREDICTORS; NONPROFIT; EDUCATION; ECONOMY; CROWD